Hirearki Peraturan Perundang-Undangan Indonesia - Muhammad Naufal Hakim (Ethics and Law Journal: Business and Notary, 2024)
Regarding the hierarchy of laws and regulations, there are two issues that are often discussed. First, whether or not to include the People's Consultative Assembly (MPR) Decree in the hierarchy of laws and regulations (Article 7 paragraph (1) of Law 12/2011). Second, the relevance of the inclusion of regulations of state institutions, agencies, or commissions such as regulations of the House of Representatives (DPR), the Regional Representatives Council (DPD), and even Regulations of the Supreme Audit Agency (BPK) or Bank Indonesia as statutory regulations (Article 8 paragraph (1) of Law 12/2011). The key questions to discuss both are: what types of regulations can be categorized as laws and regulations, so that they can be arranged in a hierarchy? These types need to be explored from the aspect of post-amendment state institutions of the 1945 Constitution as well as the theory and practice of state administration. The author concludes that the MPR Decree does not need to be included in the types and hierarchy of laws and regulations stipulated in Article 7 paragraph (1) of Law 12/2011. Therefore, there needs to be an amendment to Article 7 paragraph (1) to remove MPR Decrees from the list. On the other hand, the DPR needs to fulfill its unwritten political duty to ensure that all laws mandated by the "old MPR" are made. Abstrak Berkaitan dengan hierarki peraturan perundang-undangan, ada dua soal yang sering dibahas. Pertama, mengenai perlu atau tidaknya memasukkan Ketetapan Majelis Permusyawaratan Rakyat (MPR) ke dalam hierarki peraturan perundang-undangan (Pasal 7 ayat (1) UU 12/2011). Kedua, relevansi masuknya peraturan-peraturan lembaga negara, badan, atau komisi seperti peraturan Dewan Perwakilan Rakyat (DPR), Dewan Perwakilan Daerah (DPD), bahkan Peraturan Badan Pemeriksa Keuangan (BPK) atau Bank Indonesia sebagai peraturan perundang-undangan (Pasal 8 ayat (1) UU 12/2011). Pertanyaan kunci untuk membahas keduanya adalah: jenis-jenis peraturan apa yang dapat dikategorikan sebagai peraturan perundang-undangan, sehingga dapat disusun dalam suatu hierarki? Jenisjenis ini perlu digali dari aspek lembaga-lembaga negara pasca-amandemen UUD 1945 serta teori dan praktik penyelenggaraan negara. Penulis menyimpulkan bahwa Ketetapan MPR tidak perlu masuk ke dalam jenis dan hierarki peraturan perundang-undangan yang diatur dalam Pasal 7 ayat (1) UU 12/2011. Oleh karena itu, perlu ada perubahan Pasal 7 ayat (1) untuk mengeluarkan Ketetapan MPR dari daftar. Sementara di sisi lainnya, DPR perlu melaksanakan tugas politiknya yang tidak tertulis, untuk memastikan bahwa semua undang-undang yang diamanatkan oleh “MPR lama” dibuat. Kata Kunci: Hirearki, Undang-Undang, Indonesia